Entrepreneurship dalam Perspektif Islam; Meneguhkan Paradigma Pertautan Agama dengan Ekonomi - Mohammad Darwis (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
This paper is intended as an additional theoretical insight on the urgency of entrepreneurship, especially in the Indonesian context. Exposure of entrepreneurship in this paper is based on the paradigm of the relation of religious values ​​of the sacred, with economic behavior perceived as something profane. The discussion in this paper begins with a review that reveals the urgency of entrepreneurship in the context of economic development in Indonesia, especially since the beginning of the Asian Economic Community. Discourse of the importance of entrepreneurship is louder voiced by experts because Indonesia is still considered less ready to face free competition. This is allegedly due to the lack of entrepreneurs owned by Indonesia compared to other Asian countries. On the other side of Indonesia, the majority of the population is the Muslims are still entangled with high unemployment and poverty. At this point enggel in this paper is taken, namely the linkage of cultural values ​​and religion with the economic behavior of society in the context of Indonesianness. For that in this paper reviewed about the concept debate from the experts who discuss the relationship between the two entities. Furthermore, the exposure is continued by putting forward the general theory of entrepreneurship as well as the basic discussion about entrepreneurship in Islamic perspectives. Concluding remarks and recommendations for the scientific writing about entrepreneurship more improved both in quantity and quality.